Priorities in Chronic nonbacterial osteomyelitis (CNO) - results from an international survey and roundtable discussions - M. Mohanna; E. Roberts; L. Whitty; J. F. Gritzfeld; C. E. Pain; H. J. Girschick; J. Preston; M. Hadjittofi; C. Anderson; P. J. Ferguson; A. Theos; C. M. Hedrich (BMC, 2023)
Abstract Objective Chronic nonbacterial osteomyelitis (CNO) is an autoinflammatory bone disorder that predominantly affects children and young people. The pathophysiology and molecular mechanisms of CNO remain poorly understood, and diagnostic criteria and biomarkers are lacking. As a result, treatment is empiric and follows personal experience, case series and expert consensus plans. Methods A survey was designed to gain insight on clinician and patient experiences of diagnosing and treating CNO and to collate opinions on research priorities. A version containing 24 questions was circulated among international expert clinicians and clinical academics (27 contacted, 21 responses). An equivalent questionnaire containing 20 questions was shared to explore the experience and priorities of CNO patients and family members (93 responses). Results Responses were used to select topics for four moderated roundtable discussions at the "International Conference on CNO and autoinflammatory bone disease" (Liverpool, United Kingdom, May 25-26th, 2022). The group identified deciphering the pathophysiology of CNO to be the highest priority, followed by clinical trials, necessary outcome measures and classification criteria. Surprisingly, mental wellbeing scored behind these items. Conclusions Agreement exists among clinicians, academics, patients and families that deciphering the pathophysiology of CNO is of highest priority to inform clinical trials that will allow for the approval of medications for the treatment of CNO by regulatory agencies.